Gamma Delta T Cell Therapy for Cancer: It Is Good to be Local - Pauza, C. David; Liou, Mei-Ling; Lahusen, Tyler; Xiao, Lingzhi; Lapidus, Rena G.; Cairo, Cristiana; Li, Haishan (Frontiers in Immunology, 2018)
Human gamma delta T cells have extraordinary properties including the capacity for tumor cell killing. The major gamma delta T cell subset in human beings is designated V9V2 and is activated by intermediates of isoprenoid biosynthesis or aminobisphosphonate inhibitors of farnesyldiphosphate synthase. Activated cells are potent for killing a broad range of tumor cells in and demonstrated the capacity for tumor reduction in murine xenotransplant tumor models. Translating these findings to the clinic produced promising initial results but greater potency is needed. Here, we review the literature on gamma delta T cells in cancer therapy with emphasis on the V9V2 T cell subset. Our goal was to examine obstacles preventing effective V9V2 T cell therapy and strategies for overcoming them. We focus on the potential for local activation of V9V2 T cells within the tumor environment, to increase potency and achieve objective responses during cancer therapy. The gamma delta T cells and especially the V9V2 T cell subset, have the potential to overcome many problems in cancer therapy especially for tumors with no known treatment, lacking tumor-specific antigens for targeting by antibodies and CAR-T, or unresponsive to immune checkpoint inhibitors. Translation of amazing work from many laboratories studying gamma delta T cells is needed to fulfill the promise of effective and safe cancer immunotherapy.